Studies on yield stability in autumn wheat species - Kutasy, Erika; Csajbók, József (Acta Agraria Debreceniensis, 2001)
The environmental adaptability of crop production is basically determined by the selection of biological background (plant species and varieties) suitable for the region and the site. The sowing structure adapted to the ecological background increases the yield and decreases the yield fluctuation caused natural effects. Exact long-term trials are essential to develop variety structure of winter wheat production suitable for the given ecological conditions. We have examined the productivity and yield stability of genetically different state registered winter wheat varieties. We have compared the varieties’ yield results in plot trials, at similar agrotechnical conditions, in different cropyears. We have examined the absolute and relative (compared to the mean of varieties) yield of winter wheat varieties. We have valued the yield stability of genotypes with the help of analysis of variance and linear regression equations. We have defined the connection between productivity and yield stability of varieties. We have pointed out the varieties with good productivity and yield stability in given agroecological conditions. According to the results of our examinations the developing of variety structure suitable for the agroecological conditions could increase the potential and effective yield level of wheat production.